Evaluasi Lahan Tambak untuk Budidaya Rumput Laut Gracilaria sp di Kabupaten Bone - Sukri, Irwansyah; Arfan, Amal; Nasiah, Nasiah (LaGeografia, 2020)
This study is survey research that aims to evaluate the feasibility of ponds for the cultivation of Gracilaria sp. The number of sample points is 6 determined by using a purposive sampling method based on the location and source of water of the pond in Tellu Siattinge District, Bone Regency. Measurement of physical-chemical parameters each station I, II, III, IV, V, VI showed that temperature of 34, 32, 32, 31, 32, 31 Â° C, depth of 40, 47, 45, 45, 50, 52 cm, brightness of 87, 85, 73, 78, 60, 63%, water pH 6.5, 7, 6.5, 6.5, 7, 7, dissolved oxygen (DO) 4.1, 2.6 , 7.8, 3.5, 2.1, 3.5 ppm, salinity of 14, 16, 20, 21, 25, 25 ppt, phosphorus content 0.017, 0.015, 0.018, 0.023, 0.014, 0.021 ppm, nitrate levels 0.011, 0.15, 0.29, 0.021, 0.011, 0.023 ppm, bottom of the pond are clay except station VI with clay loam, and all ponds locations sheltered from strong winds and strong waves. The result of the study showed that station II, III, IV, and VI are classes S1 (suitable), whereas at the station I and V are classes S2.